Evaluation of the Effect of Treatment with Clear Aligners Orthodontic Appliances on The health of Periodontal Tissues (Latakia University Journal -Medical Sciences Series, 2024)
Background &Aims :This study aims to evaluate the effect of treatment with clear aligners orthodontic appliances the health of periodontal tissues  and bacterial plaque accumulation. Materials and methods: the study sample consisted of 15 patients with class 1 type1 malocclusion and moderate crowding .Plaque index (PI) Gingival Index (GI) were evaluated at 4-time points: Before treatment (T0), 1 month later (T1),3 month later(T2),6 month later(T3).Results: there was increase of gingival after 1 month of treatment in comparison with T0 (P=0.000).Plaque index degree also increased at all periods of assessment and peaked on the first month following appliance placement (P=0.000),while after 6 month  there were no significant differences in comparison with (P=0.905)Conclusions: These results suggest that using Clear aligners orthodontic appliances is associated with increase gingival during the first month of treatment because of the attachments ,and caused a moderate to mild increase in plaque accumulation during treatment